Growth and reproductive performances of farmed timorensis deer, Cervus timorensis - Zakaria, M. Alif; Saad, Mohd Zamri; Abu Hassim, Hasliza; Haron, Abd Wahid (Universiti Putra Malaysia Press, 2016)
A retrospective study was conducted to evaluate the growth and reproductive performances of timorensis deer, Cervus timorensis, that were kept in farm. All 140 animals were allowed to graze at all times while supplemented feed of approximately 1 kg/animal/day was provided except during the rainy season between October and December when supplementation was 2 kg/animal/day. Available farm records between 2011 and 2014 were collected and analysed for growth and reproductive performances. Most fawning occurred between October and December (average rainfall 413 mm) with an apparent peak in December. Average annual fawning percentage for the past four years was 57% while the average rate of mortality for fawns and adults was 5.4% and 13.5%, respectively. The average daily weight gain for up to one year of age was 0.042±0.02 kg but after one year it was 0.052±0.01 kg. The average body weight of adult timorensis at 24 months old was 48.5±1.4 and 44.5±0.9 kg for male and female, respectively. Monthly rainfall showed significant (p<0.05) negative correlation with the ADG but showed positive correlation (p<0.05) with fawning. Body weight gain was high during the dry months of May and August (average rainfall 150 mm). There seemed to be a clear breeding season for timorensis deer in this study, which was within the moderate months of March to April (average rainfall 236 mm) when body weight started to increase.